Deciphering the significance of neutrophil to lymphocyte and monocyte to lymphocyte ratios in tuberculosis: A case-control study from southern India [version 2; peer review: 2 approved] - Poorva Bakshi; Shikha Jayasheelan; Rakshatha Nayak; Sharada Rai (F1000Research)
Background Diagnosis of tuberculosis (TB) in resource-limited countries relies primarily on bacteriological confirmation using Ziehl-Neelsen (ZN) stain on sputum or other representative samples. However, this method has low sensitivity due to suboptimal sampling and techniques. While AFB culture remains a gold standard for diagnosing TB and other mycobacterial infections, its limitations include slow turnaround time, and the requirement for specialized resources and expertise. Neutrophils, monocytes, and lymphocytes are crucial in the pathogenesis of granulomatous inflammation and immune reactions. We investigated the usefulness of the haematological parameters and their ratios, like the Neutrophil to Lymphocyte ratio (NLR) and Monocyte to Lymphocyte ratio (MLR), for diagnosing tuberculosis. Methods We retrospectively grouped 114 patients with fever into those diagnosed with TB and control groups. We obtained their haematological data and calculated their derived ratios. The ratios obtained from the two groups were compared. Their sensitivity and specificity were calculated. Results Haematological parameters like MLR were higher in TB patients than in the control group. Although NLR was not significantly increased, MLR was significantly increased with p values <0.05. These tests had low sensitivity but high specificity. Conclusion Serum NLR and MLR emerge as valuable tools in TB diagnosis. Their simplicity and cost-effectiveness render them particularly suitable for screening and recurrence monitoring in rural and remote settings, thereby mitigating loss to follow-up.